APROXIMACIONES COGNITIVO-INTERACCIONISTAS AL APRENDIZAJE DE SEGUNDAS LENGUAS MEDIANTE TAREAS - Ortega, Lourdes (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Task-based language learning constitutes one of the most popular proposals for second language pedagogy in the last fifteen years, and it is also a burgeoning research area within instructed second language acquisition. Yet, several distinct traditions have evolved whose differences are too often ignored in specialized discussions. In the present article, I offer an overview of four cognitive-interactionist approaches to the investigation of task-based language learning. I map their historical roots and the main theoretical arguments each makes for competence-expanding benefits. I also evaluate the research methodologies underlying each of these four traditions, identifying major challenges that await each program if the full pontential of task-based language pedagogies for improving instructed second language acquisition is to be better understood.